(untitled) (Research, Society and Development, 2020)
The concern with organizational learning parallel to the incorporation of technologies in the processes of training, development and education in public and private organizations brought a new look to Corporate Education. In this context, this article aimed to analyze organizational learning practices in institutional schools in the state of Mato Grosso in relation to Distance Corporate Education (ECAD). Specifically, we sought to map organizations, describe practices and identify their organizational learning processes. This was a qualitative research, conducted through semi-structured interviews with managers of 06 (six) state public sector organizations that have distance corporate education practices in the Training, Development and Education (TD&E) programs. Such enabling agencies have a target audience of 123,100 (one hundred and twenty-three thousand and one hundred) public servants distributed in all 141 (one hundred and forty-one) municipalities in the state of Mato Grosso. In addition, they have a reduced team for the performance of ECAD functions. The presence of Experiential Learning was identified in the ECAD of the Interviewed Corporate Schools. It was found that Corporate Schools develop experiential learning strategies seeking resources in formal learning processes, with specialists by itself.